Crack initiation life model for compression-compression low cycle fatigue based on damage mechanics. (April 2023) - Dong, Qi; Shi, Xinhong; Tong, Dihua; Liu, Fengrui; Wang, Linjuan; Zhao, Libin
Highlights: Establish a crack initiation life model for compression-compression low cycle fatigue. The plastic strain range is modified by the offset distance of the hysteresis loop. Carry out the crack initiation experiments for compression-compression low cycle fatigue. The predicted life of the model is in good agreement with the experimental value. Abstract: A crack initiation life model for compression-compression low cycle fatigue was proposed, based on crack initiation life damage mechanical model for tension-compression low cycle fatigue. This work used the offset distance of the hysteresis loop, in the form of a double power function, to modify the plastic strain range. Six groups of crack initiation experiments were carried out. The crack initiation life predicted by the model proposed in this work and the model for tension-compression low cycle fatigue were compared with the experimental values. The results indicate that the model proposed can obtain an effective prediction.